The Contribution Of Physical And Sports Education To Reducing The Behavior Of Physical And Verbal Violence Among Adolescents - Benziane , Tahar; Tafiroult , Billal (sports creativity, 2025)
The study aimed to identify the effect of physical and sports education on the behavior of physical and verbal violence among middle school students. The problem of the study on the differences between practitioners and non-practitioners of physical education was in the measure of violence in the middle among students. This study was limited to the opinions of a sample of 200 students studying in intermediate education distributed over four averages in the city of Laghouat, chosen randomly. For the purposes of this study, the researcher used the descriptive approach, and after statistical treatment with the SPSS program and data analysis, the researcher reached the following results: There are statistically significant differences between practitioners and non-practitioners of physical education in the scale of violence (verbal and physical) among middle school students